Zombies in Tondela : Watching I’ll See You In My Dreams (2003) - Martins, Ana Rita (2017)
Monsters have attracted our imagination throughout times, even in an apparently rational and pragmatic age such as ours. Being one of the monsters of the new millennium, the zombie is now a permanent figure of popular culture, both embodying society’s most terrible fears and exploring audience’s desire for violent cathartic experiences. Of African origins, the zombie has been popularised by American cinema and spread across cultures and media. Although with no great tradition of horror, Portugal also has an example of the zombiemania that seems to have overtaken the world, the short film I’ll See You In My Dreams (2003, Dir. Miguel Angél Vivas, Prod. Filipe Melo). This article aims at questioning the concept of monster in general terms, then look at the evolution of the zombie as a monstrous figure in particular and, finally, analyse that which is considered the first Portuguese zombie film, contextualising it in relation to global zombie representations.